Algorytm jako tworzywo artystyczne. O poszukiwaniu nowych strategii komunikacyjnych w sztukach wizualnych i performatywnych - Wachowski, Jacek (Przestrzenie Teorii, 2025)
This article presents artistic practices that utilize algorithmic techniques, emerging at the intersection of art, science, and technology. It seems that artists employ algorithms: 1) to create graphic formats (both static and dynamic); 2) to perform supervisory functions related to controlling devices and objects, as well as controlling their scope of operation; and 3) to design communication patterns (between machines and between machines and humans). In addition to expanding the scope of experimentation, algorithms implemented in artistic practices also prompt a reassessment of fundamental aesthetic concepts. They pose questions from the cognitive universe that interest representatives of numerous disciplines (humanities, philosophy, computer science, and technical sciences). Their goal is not only to attempt to domesticate exotic practices but also to reflect on ways of thinking about them and methods of researching them.